The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.17221/1/2010-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Potassium and calcium enrichment alleviate salinity-induced stress in hydroponically grown endives

Abstract: Tzortzakis N.G., 2010. Potassium and calcium enrichment alleviate salinity-induced stress in hydroponically grown endives. Hort. Sci. (Prague), 37: 155-162.Salinity either of soil or of irrigation water causes disturbance in plant growth and nutrient balance and reduces crop yields. The effects of NaCl salinity and/or calcium or potassium level on the plant growth and severity of gray mold (Botrytis cinerea [De Bary] Whetzel) were investigated in endive (Cichorium endivia L., cv. Green Curled) grown with the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 27 publications
2
25
1
1
Order By: Relevance
“…1a). Similar results have been reported by Tzortzakis (2010) and Ashraf et al (2013), who showed that application of potash fertilizer decreases the toxic effects of salinity on growth, as well as plant biochemical and physiological processes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…1a). Similar results have been reported by Tzortzakis (2010) and Ashraf et al (2013), who showed that application of potash fertilizer decreases the toxic effects of salinity on growth, as well as plant biochemical and physiological processes.…”
Section: Discussionsupporting
confidence: 90%
“…They showed that N and K + contents decrease in stressed environment and with the application of nutrients like potassium, the uptake of essential nutrients i.e., Ca 2+ , K + and Mg 2+ can increase followed by proper regulation of all metabolic activities, and resulting in an improvement of growth and productivity. Tzortzakis (2010) and Ashraf et al (2015) also state that K + is a vital nutrient and growth of plants depends upon its availability. Both wheat cultivars showed positive response to K 2 SO 4 and absorption of potassium nutrients (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…8; effect of salt stress was alleviated on the lengths of roots. Same was reported by Ashraf et al (2013) and Tzortzakis (2010) that supplementary potassium reduced the effects of salt stress on the growth of plants (Wang et al, 2013).…”
Section: Shoot and Root Lengthssupporting
confidence: 70%
“…Similar findings are also depicted by that salt stress negatively effect the plant growth and development in such a way that many metabolic processes bcomes hinders because of nitrogen deficiency in plants. It is also reported that potassium is essential nutrients and growth of plants increased in the potassium fertilizer and there is more absorption of nitrogen contents by the use of fertilizer as investigated by Tzortzakis (2010) and Ashraf et al (2013).…”
Section: Nitrogen Contents Of Roots and Shoots (Mg/g Dry Wt)mentioning
confidence: 98%
See 1 more Smart Citation